Inhalation and inflammation: examining aeroallergens and eosinophilic esophagitis - Sekar, Sitharthan; Kelly, Kate; Sheth, Dipa; Papademetriou, Marianna (Frontiers in Allergy, 2025)
Eosinophilic esophagitis (EoE) is a chronic immune-mediated disease leading to inflammation in the esophageal lining. EoE has become a significant cause of gastrointestinal illness in both children and adults. While there is significant focus on dietary triggers in the pathophysiology of the disease, aeroallergens are also increasingly implicated in both the development and clinical presentation. Possible mechanisms, seasonality and current evidence for the role of aeroallergens in EoE are discussed, including seasonality, allergen specific mechanisms and therapeutic options. A multidisciplinary team between allergists and gastroenterologists is optimal for coordinated patient management.